The Effectiveness of Using Picture Books to Strengthen Students’ Performance in Reading Comprehension - Putri Ratna Sari; Dohra Fitrisia (Research in English and Education Journal, 2022)
This research is a library study that analyzes how the use of picture books can improve students’ reading ability based on some experts and previous studies. This study focuses on the theory by Honig, Diamond, and Gutlohn (2008) that can be categorized into three activities, which are initial steps, main activities’ steps, and post activities steps. Data collection is done using discourse investigation technique on text books, articles, journals, research papers and other data sources of high relevance. There are 5 sources in this study, those sources are: Dameiyanti (2019), Laraswati (2018), Jusmini (2017), Roslina (2017), and Subekti (2014). Here, the researcher perform the analyses by reading comprehensively to acquire an understanding of the important data from all sources. The researcher analyses to find similarities or relationships between one source and the other. Afterwards, the researcher paraphrases and breaks down the statements to obtain valuable information. Findings from the data selected are explained and summarized by including the name of the researcher, methodology, text type, students’ background, field of study, instruction procedure, learning outcomes, advantages and disadvantages of the technique. The results of the analysis of all the sources  show that the use of picture book can improve students’ reading capability.